2014
DOI: 10.1002/cncr.28631
|View full text |Cite
|
Sign up to set email alerts
|

Disparity in perceptions of disease characteristics, treatment effectiveness, and factors influencing treatment adherence between physicians and patients with myelodysplastic syndromes

Abstract: BACKGROUND: Previous studies have suggested that many patients with myelodysplastic syndromes (MDS) have an incomplete understanding of their disease, which may influence adherence to prescribed regimens and outcomes. METHODS: To better understand physician and patient perceptions about MDS and MDS therapy, the authors conducted 2 surveys in February 2012: 1 for patients with MDS and 1 for health care professionals (HCPs) who cared for patients with MDS. Patient and HCP surveys consisted of 57 and 49 questions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 23 publications
0
33
0
Order By: Relevance
“…78,79 This semantic distinction influences patient self-perception and has practical consequences for regulatory jurisdiction, health care resource allocation, cancer-specific indemnity policy payouts, and research funding eligibility.…”
Section: Is Chip or Mds Cancer?mentioning
confidence: 99%
“…78,79 This semantic distinction influences patient self-perception and has practical consequences for regulatory jurisdiction, health care resource allocation, cancer-specific indemnity policy payouts, and research funding eligibility.…”
Section: Is Chip or Mds Cancer?mentioning
confidence: 99%
“…Perhaps more important is education of patients and physicians, many of whom in a recent survey seemed unaware of the potential for HSCT to cure patients with MDS. 126 The current number of patients undergoing SCT in the United States is only a small fraction of those who are potential candidates for the procedure, as many patients lack a donor, choose not to undergo HSCT because of concerns about changes in quality of life or fear of adverse events, or are never referred to a center where HSCT can be performed.…”
Section: Developments In Mds 2799mentioning
confidence: 99%
“…31,32 Perhaps, as a result, one study suggested that approximately half of MDS patients favor a passive role in treatment decision-making, 33 making clinician recommendations the primary driver of most treatment decisions. Our data suggest that QOL concerns may not be routinely incorporated in the treatment decision-making for older patients with MDS.…”
Section: Discussionmentioning
confidence: 99%